232 Psychotropic Medication Use Before Cancer Diagnosis Among US Adolescents and Young Adults. (April 2022) - Onasanya, Oluwadamilola; dosReis, Susan; Castillo, Wendy Camelo
Abstract : OBJECTIVES/GOALS: To describe the prevalence of, and factors associated with, psychotropic medication use before cancer diagnosis (solid tumor cancer, lymphoma or leukemia) among AYAs 15 to 39 years of age in the US. METHODS/STUDY POPULATION: Retrospective cohort study in a 10% sample of claims from the IQVIA PharMetricsÂ® Plus for Academics (2006-2020). We included AYAs with no prior cancer diagnosis codes 9 months before their index date – defined as the first of â‰¥2 ICD-9/10-CM primary diagnosis codes for cancer occurring â‰¤60 days apart. We defined psychotropic use as a claim for an antidepressant, anxiolytic/sedative-hypnotic, mood stabilizer, stimulant or antipsychotic medication. Prevalence of psychotropic use overall and by class, was estimated as the proportion of AYAs with at least one claim for a psychotropic in the 9-months prior to the index date. Using Chi-square and T-tests, we compared demographic characteristics, prevalence of mental health disorders, chronic pain and cancer type between psychotropic users and non-users. RESULTS/ANTICIPATED RESULTS: We identified 6, 257 AYAs with cancer (thyroid 17%, breast 13%, melanoma 13%), 64% female, mean age 31 (SD 6) years. Twenty-four percent (n=1, 506) used a psychotropic in the 9 months prior to the index date. Psychotropic classes used were antidepressants 15%, anxiolytic/sedative-hypnotics 11%, stimulants 3%, mood stabilizers 2% and antipsychotics 1%. Psychotropic use was higher among females than males (27% vs 19%, p <.001), older than younger AYAs (35 to 39 years-old: 26% vs 15 to 19 years-old: 16%, p <.001). Anxiety (25% vs 4%), depression (22% vs 3%) and chronic pain (17% vs 8%) were more common among those with psychotropic use pre-cancer diagnosis (all p <.001). The proportion of AYAs diagnosed with brain cancer was higher among psychotropic users than non-users (7% vs 5%, p <.001). DISCUSSION/SIGNIFICANCE: One in four US AYAs used a psychotropic medication prior to being diagnosed with cancer. Understanding psychotropic medication management patterns for these patients before cancer treatment may help inform comprehensive care.